Tuberculosis risk from exposure to solid fuel smoke: a systematic review and meta-analysis. - Kurmi, O; Sadhra, C; Ayres, J; Sadhra, S (2014)
BACKGROUND: Studies, particularly from low-income and middle-income countries, suggest that exposure to smoke from household air pollution (HAP) may be a risk factor for tuberculosis. The primary aim of this study was to quantify the risk of tuberculosis from HAP and explore bias and identify possible causes for heterogeneity in reported effect sizes. METHODS: A systematic review was conducted from original studies. Meta-analysis was performed using a random effects model, with results presented as a pooled effect estimate (EE) with 95% CI. Heterogeneity between studies was assessed. RESULTS: Twelve studies that considered active tuberculosis and reported adjusted effect sizes were included in the meta-analyses. The overall pooled EE (OR, 95% CI) showed a significant adverse effect (1.43, 1.07 to 1.91) and with significant heterogeneity between studies (I(2)=70.8%, p<0.001). When considering studies of cases diagnosed microbiologically, the pooled EE approached significance (1.26, 0.95 to 1.68). The pooled EE (OR, 95% CI) was significantly higher among those exposed only to biomass smoke (1.49, 1.08 to 2.05) when compared with the use of kerosene only (0.70, 0.13 to 3.87). Similarly, the pooled EE among women (1.61, 0.73 to 3.57) was greater than when both genders were combined (1.39, 1.01 to 1.92). There was no publication bias (Egger plot, p=0.136). Significant heterogeneity was observed in the diagnostic criteria for tuberculosis (coefficient=0.38, p=0.042). CONCLUSIONS: Biomass smoke is a significant risk factor for active tuberculosis. Most of the studies were small with limited information on measures of HAP.